2010
DOI: 10.1051/apido/2009075
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression ofmajor royal jelly protein 1gene in the mushroom bodies of worker honeybees with reduced learning ability

Abstract: Reduced expression of major royal jelly protein 1 gene in the mushroom bodies of worker honeybees with reduced learning ability. Apidologie, Springer Verlag, 2010, 41 (2), Abstract -The learning ability of European honeybees, Apis mellifera, develops with age. However, when worker bees are isolated from their colony and are fed only sucrose solution, their learning development is hindered. This rearing method has allowed us to compare worker bees of the same age but with different learning abilities. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 54 publications
1
53
0
2
Order By: Relevance
“…Kucharski et al (1998) reported mrjp1 expression in the Kenyon cells of the mushroom bodies in the honeybee brain, a new, then unknown function for MRJPs. The expression of mrjp1 in the mushroom bodies was higher in worker bees sampled from colonies compared to isolated ones (Hojo et al, 2010), that are known to have a decreased learning ability (Ichikawa & Sasaki, 2003). MRJP1 was found to be up-regulated in nurses compared to queens, foragers or drones and to be located in the antennal lobe, optical lobe and mushroom bodies Peixoto et al, 2009).…”
Section: Expression and Synthesis Of Mrjpsmentioning
confidence: 96%
See 3 more Smart Citations
“…Kucharski et al (1998) reported mrjp1 expression in the Kenyon cells of the mushroom bodies in the honeybee brain, a new, then unknown function for MRJPs. The expression of mrjp1 in the mushroom bodies was higher in worker bees sampled from colonies compared to isolated ones (Hojo et al, 2010), that are known to have a decreased learning ability (Ichikawa & Sasaki, 2003). MRJP1 was found to be up-regulated in nurses compared to queens, foragers or drones and to be located in the antennal lobe, optical lobe and mushroom bodies Peixoto et al, 2009).…”
Section: Expression and Synthesis Of Mrjpsmentioning
confidence: 96%
“…In addition, workers in colonies where the queen is lost activate their ovaries to produce eggs and synthesize MRJP1 and 2 in their glands like normal nurse bees (Nakaoka, Takeuchi & Kubo, 2008). Since then, the expression of mrjp1-8 in the brain has been shown repeatedly (Whitfield et al, 2002;Thompson et al, 2006;Garcia et al, 2009;Peixoto et al, 2009;Hojo et al, 2010). Kucharski et al (1998) reported mrjp1 expression in the Kenyon cells of the mushroom bodies in the honeybee brain, a new, then unknown function for MRJPs.…”
Section: Expression and Synthesis Of Mrjpsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, worker- and tissue-biased expression of mrjp1 – 7 indicates spatial and functional separation from mrjp8 and 9 , suggesting neofunctionalization of an ancestral duplicate. All worker- mrjps are predominantly expressed in heads, although their spatial expression patterns indicate further differentiation–with preferential expression in hypopharyngeal glands (for those genes encoding proteins with nutritional value) and/or the brain 39 . Moreover, elevated transcript abundances of some mrjps in brood-raising nurse bees compared with foragers (and vice versa ) indicate more specialized functions related to division of labor 13 , 32 .…”
Section: Resultsmentioning
confidence: 99%